A poem on the refortification of Dorylaion in 1175 - SPINGOU, Foteini (Byzantina Symmeikta, 2012)
<!–StartFragment–> <!– /* Font Definitions */ @font-face font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:85; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:129 0 0 0 8 0; @font-face font-family:Gentium; panose-1:2 0 5 3 6 0 0 2 0 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:131 0 0 0 9 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Gentium; mso-fareast-font-family:Cambria; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Gentium; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; @page Section1 size:595.0pt 842.0pt; margin:62.35pt 89.85pt 62.35pt 89.85pt; mso-header-margin:25.5pt; mso-footer-margin:25.5pt; mso-paper-source:0; div.Section1 page:Section1; –> In the summer/autumn of 1175, Manuel Komnenos (1143-1180) undertook the rebuilding of Dorylaion, one of the major aplekta in Asia Minor. For this occasion a poem was written. The strong acquaintance of the poet with the conventions of court literature, the occasional content of the poem and its panegyric character, suggest that the text was written for a small ceremony which took place at Dorylaion. The author is probably an anonymous professional court poet who accompanied Manuel in his expedition. The authorship is further discussed since the manuscript tradition might suggest that John Tzetzes was the author. After a close look at the language, style and metre of the poem, this identification is excluded. In 1908, Spyridon Lambros published the poem on the basis of manuscript Barocci 194 (fifteenth century) of the Bodleian Library. This study re-edits the poem on the basis of two more manuscripts: manuscript Parisinus Graecus 2644 (late thirteenth century) of the Bibliothèque Nationale and Auctarium T.1.10 of the Bodleian Library (sixteenth century). The history of each manuscript is analysed and the relation between them examined. It is established that the Auctarium is a direct copy from the Parisian manuscript. The metrical analysis of the poem follows and special textual problems are discussed. Finally, the translation of the original text is provided.